Mechanistic read-across comes of age: a comparative appraisal of EFSA 2025 guidance, ECHA’s RAAF, and good read-across practice - Hartung, Thomas; Rovida, Costanza (Frontiers in Toxicology, 2025)
Read-across has matured from an expert-driven extrapolation based largely on structural analogy into a rigorously documented, mechanistically informed cornerstone of next-generation risk assessment. Three pivotal frameworks are compared that now shape its regulatory use: the European Food Safety Authority’s (EFSA) 2025 guidance for food and feed safety, the European Chemicals Agency’s (ECHA) Read-Across Assessment Framework (RAAF) for industrial chemicals under REACH, and the community-driven Good Read-Across Practice (GRAP) principles. Using five analytical lenses—conceptual structure, scientific rigor, implementation tools, regulatory acceptance, and practical impact—we identified areas of complementarity and divergence. EFSA provides a seven-step, uncertainty-anchored workflow that actively embeds new approach methodologies (NAMs) and adverse outcome pathway reasoning, offering applicants a transparent “how-to” template. RAAF, in contrast, operates as an evaluator’s rubric: six scenario types and associated assessment elements delineate what evidence must be delivered, thereby standardizing regulatory scrutiny but leaving dossier construction to the registrant. GRAP supplies the conceptual glue, emphasizing mechanistic plausibility, exhaustive analogue selection, explicit uncertainty characterization, and the strategic use of NAMs; its influence is evident in both EFSA’s and ECHA’s evolving expectations. (Terminology note: the acronym “NAM” was popularized at an ECHA workshop in 2016; earlier documents such as RAAF and initial GRAP papers therefore may not use the term explicitly). Regulatory experience under REACH demonstrates that dossier quality and acceptance rates rise markedly when RAAF criteria are met, while EFSA’s new guidance is poised to catalyze similar gains in food and feed assessments. Globally, the convergence of these frameworks—reinforced by OECD initiatives and NAM-enhanced case studies—signals an emerging international consensus on what constitutes defensible read-across. In conclusion, harmonizing EFSA’s procedural roadmap with RAAF’s evaluative rigor and GRAP’s best-practice ethos can mainstream reliable, animal-saving read-across across regulatory domains, paving the way for fully mechanistic, AI-enabled chemical safety assessment.